Endovascular approach for acute limb ischemia without thrombolytic therapy. (May 2020) - Fukuda, Keisuke; Yokoi, Yoshiaki
Background: Endovascular therapy for acute lower limb ischemia (ALLI) has developed and demonstrated safety and efficacy. The purpose of this study was to assess clinical outcomes in patients treated for ALLI with conventional endovascular or surgical revascularization. Method: This study was a retrospective single-center review. Consecutive patients with ALLI treated with conventional endovascular revascularization (ER) without thrombolytic agent or surgical revascularization (SR) between 2008 and 2014 were investigated. The 1 year and 3 year amputation rate and mortality rate were assessed by time-to-event methods, including Kaplan–Meier estimation. Result: A total of 64 limbs in 62 patients with ALLI due to thromboembolism or thrombosis of a native artery, bypass graft, or previous stented vessel were included. The majority of limbs (90.9%) presented with Rutherford clinical categories 1 to 2 ischemia. Technical success rate was 95.5% in ER and 92.9% in SR group ( p = 0.547). Overall amputation rates were 9.1% in ER versus 9.5% in SR after 1 year ( p = 0.971) and 9.1% in ER versus 11.9% in SR after 3 year ( p = 0.742). Overall mortality rates were 15% in ER versus 7.1% in SR after 1 year ( p = 0.491) and 15% in ER versus 11.2% in SR after 3 year ( p = 0.878). Conclusion: Endovascular or surgical revascularization of ALLI resulted in comparable outcomes in limb salvage and mortality rate at 1 year and 3 year. Conventional endovascular therapy without thrombolytic agent such as stenting, balloon angioplasty, or catheter-directed thrombosuction may be considered as a treatment option for ALLI.